Penentuan Lokasi Stasiun Pengisian Bahan Bakar Umum (SPBU) Baru Dengan Menggunakan Metode ELECTRE III (Studi Kasus PT.Pertamina Surabaya) - Adiprasetya, Rachmat; Sukmaaji, Anjik; Taufik, Vicky Mohammad (Jurnal JSIKA, 2014)
Gas StationÂ hasÂ become important facilitiesÂ for todayâs society especially in the big cities such as Surabaya, This is due to public demand for fuel increase from year to year. With that many demand of fuel make businessman think that the gas station business is promising. However in Surabaya there are quite a lot gas station so the competition is getting tougher. In order for gas station can gain a great benefit, businessman is required to consider the factor that can support the hustle of gas station. That factor such as good service, facilities provided by the gas station, strategic location, and etc.Among these factor the most important is the selection ofÂ strategic location. To assist businessman in the selection of strategic location for the construction of gas station can be solved by the application of determining the location of new gas station in Surabaya. Determining the new location of new gas station in Surabaya using ELECTRE III as the method to get the recommended location that fits with the criteria of PT.Pertamina. The Results of this study are recommendations gas stations locations in the city of Surabaya based on ELECTRE III method. This system is expected to help making decisions and facilitate investor, businessman or related parties can obtain information to construct gas station in the area with potential and strategic that fulfill the criteria and based on the data obtained from various parties.